2018
DOI: 10.1088/1748-9326/aaea84
|View full text |Cite
|
Sign up to set email alerts
|

Global terrestrial stilling: does Earth’s greening play a role?

Abstract: Previous studies have documented that surface wind speed (u) has been increasing over the ocean but decreasing over land for the past several decades. The decreasing u at the surface over land has been referred to as terrestrial stilling. A plausible hypothesis for terrestrial stilling is an increase in surface roughness associated with changes in land surface (e.g. enhanced vegetation growth, landscape fragmentation or urbanization). One of the most widespread land surface changes is enhanced vegetation leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
1
26
1
1
Order By: Relevance
“…Despite these limitations, this study rejected the hypothesis that urbanization was a dominant driver of regional terrestrial stilling in the urban areas of the Beijing-Tianjin-Hebei region. Given the minor role of vegetation growth in NSWS change (Zeng et al 2018), it appears that the observed decrease in NSWS over this region was probably driven by the natural internal variability of the climate system and/or large-scale anthropogenic climate changes. In the case of JRA-55 reanalysis, we found that a clear understanding of the interactions and couplings among the surface layer, planetary boundary layer and free atmosphere was a prerequisite to accurately reproduce historical and future NSWS changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these limitations, this study rejected the hypothesis that urbanization was a dominant driver of regional terrestrial stilling in the urban areas of the Beijing-Tianjin-Hebei region. Given the minor role of vegetation growth in NSWS change (Zeng et al 2018), it appears that the observed decrease in NSWS over this region was probably driven by the natural internal variability of the climate system and/or large-scale anthropogenic climate changes. In the case of JRA-55 reanalysis, we found that a clear understanding of the interactions and couplings among the surface layer, planetary boundary layer and free atmosphere was a prerequisite to accurately reproduce historical and future NSWS changes.…”
Section: Discussionmentioning
confidence: 99%
“…Beijing-Tianjin-Hebei, Yangtze River Delta, Pearl River Delta, and North China Plain) were relatively small. At the global scale, besides northern China, rapid declines in NSWS were also observed in eastern North America, northeastern Europe, Siberia and even over the Tibetan Plateau (You et al 2014, Zeng et al 2018, Zhang et al 2019b, where urbanization is very slow or negligible. A recent study indicated that decadal-scale variations of NSWS was dictated by internal decadal climate variabilities, rather than by the local impact of urbanization (Zeng et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wind stilling has been reported as an important phenomenon in recent decades (Roderick et al 2007, Vautard et al 2010 as the observed land-surface wind speed has decreased in a number of regions (Bichet et al 2012, Wu et al 2018, Zeng et al 2018. By analyzing the observations at 822 surface weather stations, Vautard et al (2010) showed that the surface wind speed has been reduced by 5%-15% over almost all continents in the Northern Hemisphere (NH) midlatitudes over .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also showed a decrease in surface wind speeds and wind power potential in most of NH over the past four decades (Tian et al 2019) exerting adverse impacts on windgenerated electricity (Sherman et al 2017) and the dispersion of air pollutants (Li et al 2019b), reducing evaporation (McVicar et al 2012), and affecting soil erosion (Zhang et al 2019). However, the mechanisms related to the observed wind stilling are not well understood (Wu et al 2018, Zeng et al 2018. Moreover, climate models have limited ability for simulating the long-term trend in surface wind speeds (Jiang et al 2017, Tian et al 2019, indicating the need for a clear understanding of the mechanisms of wind stilling.…”
Section: Introductionmentioning
confidence: 99%